Comparison of Tannin Levels in Brewed and Boiled Green Tea (Camellia Sinensis (L.) Kuntze) by UV-Vis Spectrophotometric Method - Styawan, Anita Agustina; Atun Yuliana (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2024)
Introduction: Green tea (Camellia sinensis (L.) Kuntze) has antibacterial and antioxidant properties that are effective in preventing and treating diseases. Green tea contains tannin compounds with antidiarrheal properties, stops bleeding and prevents inflammation of the oral mucosa. To get its properties, the way tea is processed affects the tannin content in tea. Aims: To determine the tannin content in brewed and boiled green tea using UV-Vis Spectrophotometric method. Method: The research method used was experimental research. The sample used was green tea taken from the cultivation site "Mbok Karti" Kemuning, Ngargoyoso, Karanganyar. Extracted using the reflux method. Determination of levels analyzed by UV-Vis Spectrophotometry method. Qualitative test results using FeCl3 1% that brewed and boiled green tea contains tannins by showing a change in color to blackish green. Result: The results of quantitative tests using UV-Vis Spectrophotometry obtained a comparison of tannin levels in brewed green tea of 0.05163% w/b and boiled ones of 0.04988% w/b. Where in every 200 grams of brewed green tea samples there are 103.26 mg of tannins for boiled green tea samples there are 99.67 mg of tannins. Tannin levels in brewed green tea are greater than those boiled because tannins are damaged at temperatures above 80°C. While when boiling uses temperatures above 80°C. Whereas when boiling uses temperatures above 80°C. Conclusion: So it is concluded that brewed green tea has higher tannin levels than boiled green tea.